Optimizing Hypnotherapy-Based Counseling in Secondary Schools: Implications for Islamic Education Policy - Ferianto, Ferianto; Saprialman, Saprialman; Supardi, Edi; Gani, Ruslan Abdul; Sein, Lau Han; Hajimasamae, Muhammatkasibudi (FKIP Universitas Lampung, 2025)
Optimizing Hypnotherapy-Based Counseling in Secondary Schools: Implications for Islamic Education Policy. Objective: This study aims to analyze the effectiveness of hypnotherapy in Islamic value-based individual counseling to improve self-regulation, emotional resilience, and learning motivation among secondary school students. Method: The study used a mixed-method approach with a convergent design, combining pre-post test quantitative data with qualitative data from interviews, observations, and documentation. Quantitative data were collected using self-regulation and concentration scales, academic anxiety scales, and learning motivation scales. Qualitative data were obtained through semi-structured interviews, participatory observations, and document studies. Findings: Quantitative results showed a significant increase in self-regulation, emotional resilience, and learning motivation, as well as a significant decrease in academic anxiety. Meanwhile, qualitative findings revealed three main themes: (1) students felt calmer, more focused, and more capable of controlling their emotional resilience after participating in hypnotherapy sessions, (2) counselors emphasized the importance of consistently implementing Islamic value-based standard operating procedures (SOPs), and (3) there were administrative and ethical challenges, including the need for parental consent and school schedule adjustments. Conclusion: The integration of quantitative and qualitative data shows that hypnotherapy is effective in supporting students' emotional and academic readiness, particularly in improving self-regulation, emotional resilience, and learning motivation. However, the implementation of this strategy requires attention to ethical, regulatory, and Islamic education policy aspects so that it can be applied sustainably and relevant to the counseling service needs in secondary schools. Keywords: hypnotherapy, individual counseling management, islamic education.